Educação corporativa para sustentabilidade : análise das iniciativas de uma instituição financeira à luz das teorias de reflexão crítica - Vieira, Vanessa Mariano de Castro (2017)
Since sustainability demands a paradigm shift in production and consumption patterns, the transition to another rationality in the organization requires corporate education efforts toward the development of its professionals. This objective demands to promote the exercise of critical reflection in organizations through a corporate education that distances itself from a proposal focused on purely pragmatic and instrumental training, fostering reflection, that is, that questions assumptions and that stimulates new values and culture towards sustainability. Theories of critical reflection (CR) and transformative learning (TL) are adequate to think about Corporate Education for Sustainability (CEfS). This research was guided by the types of reflection of Mezirow (1991): the “problem solving”, focused on the reflection on content and process and "problem posing", that focuses on the criticism of the premises belonging to the problem. In addition, it is also discussed the TL and the competences that it can foster to respond to the assumptions of sustainability in the organization. The overall goal of the research is to describe and analyze CEfS initiatives triggered by a financial institution in the light of the concepts of Critical Reflection and Transforming Learning, in order to understand how such formative actions are fostering the assumptions of sustainability in the organization. The object of study were the initiatives of CEfS offered by a Brazilian financial institution (FI) considered worldwide of excellence. In order to carry out the dissertation, the case study was adopted as a research strategy, with data construction by examining documents and interviews, using the template for analysis. The documentary analysis of the educational architecture focused on sustainability of the FI was carried out, and two formative actions of this set were examined in greater detail. In addition, considering the public of these two formative actions, eleven in-depth interviews were conducted with educators and open questions were sent via email to the participants, with the return of 81 students who externalized their perceptions. These data made it possible to observe a process of oscillation between more reflexive and critical training proposals in substitution for others of a more pragmatic and instrumental nature, in the period between 2003 and 2017, due to changes in the organization 's strategic orientation in this field. As a consequence, there was a depletion of CR and TL ideas for sustainability, which are expressed in the participants' narratives about the experiences lived. The narratives directed to the reflection of the content and the process prevailed in relation to the discourses involving premise, which has clear implications for the realization of the desired paradigm changes. This study contributes to thinking about CR and TL focused on sustainability in organizations, at the same time it shows elements that are important to be considered in the analysis of formative experiences of this nature, such as the pragmatic and reflective dimension of the educational initiative; training format; continuity of such action over time; contextual character and its relation to the collaborator's work and organization´s support in the post-course. As a practical contribution, this research sought to present subsidies for the advancement and improvement of training actions aimed at the objectives of sustainable and human development in the organization, guided by the exercise of critical reflection and of purposes from transformative learning, which represents a trend of current research related to corporate education.